Competition and corporate control in partial ownership acquisitions - Torben Stühmeier (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Competition authorities have a growing interest in assessing the effects of partial ownership arrangements. We show that the effects of such agreements on competition and welfare depend on the intensity of competition in the market and on the firms' governance structure. When assessing the effects of partial ownership, competition policy has to consider both the financial interest and level of control of the acquiring firm in the target firm.
Keywords: L11; L13; L41; 330; corporate control; merger; partial acquisition